G-Protein Coupled Receptor 35 Induces Intervertebral Disc Degeneration by Mediating the Influx of Calcium Ions and Upregulating Reactive Oxygen Species. (18th January 2022) - Chen, Zhe; Jiao, Yucheng; Zhang, Ying; Wang, Qingfeng; Wu, Wenjian; Zheng, Jiancheng; Li, Jitian
Abstract : Intervertebral disc degeneration (IDD) is a chronic disease affecting millions of patients; however, its specific etiology is unknown. G protein-coupled receptors (GPRs) are a superfamily of integral membrane receptors in cells, and the receptors respond to a diverse range of stimuli and participate in multiple cellular activities. Here, using RNA-sequencing (RNA-seq) methods and immunohistochemistry, we revealed that G protein-coupled receptor 35 (GPR35) may have a relationship with IDD. Then, we demonstrated that the deletion of GPR35 in nucleus pulposus cells (NPCs) with siRNA or in Gpr35 -/- mice significantly alleviated IDD caused by senescence or mechanical stress, further validating the pathological role of GPR35 in IDD. In addition, GPR35 induced the influx of Ca 2+ and upregulation of reactive oxygen species (ROS) under mechanical stress in NPCs, which we believe to be the mechanism of GPR35-induced IDD. Finally, GPR35 caused upregulation of ROS in NPCs under mechanical stress, while excessive ROS stimulated the NPCs to express more GPR35 with a significant dose or time response. The u-regulated GPR35 could sense mechanical stress to produce more ROS and perpetuate this harmful cycle. In summary, our study shows that GPR35 plays a critical role in mediating IDD via mediating the influx of calcium ions and upregulating ROS, which implies a strong potential advantage of GPR35 as a prevention and treatment target in IDD.